Assessment of inflammatory parameters in obstructive coronary artery disease and cardiac syndrome X: an evolving value of neutrophil-lymphocyte ratio - Boyraz, Bedrettin; Mutluer, Ferit Onur; Topal, Dursun; Demir, Mehmet; Peker, Tezcan; Yılmaz, Mustafa; Akgümüş, Alkame; Tenekecioğlu, Erhan (The European Research Journal, 2020)
Objectives: Atherosclerosis represents an active inflammation that leukocytes play a major role. Neutrophil-lymphocyte ratio (NLR) has been shown as an indicator of systemic inflammation. Our aim was to evaluate inflammatory markers in obstructive coronary artery disease (CAD) and cardiac syndrome X (CSX) and to evaluate NLR in predicting CAD in patients with typical chest pain and coronary risk factors. Methods: Eighty patients with CSX, 80 patients with obstructive CAD with unstable angina pectoris and a control group of 80 subjects were recruited into the study. Hematologic and biochemical parameters were investigated. Results: High-sensitive C-reactive protein (hs-CRP) was increased in CAD group and CSX group compared to the control group (p < 0.001); however it was comparable between CAD and CSX groups (p = 0.065). Mean NLR was higher in CAD group than CSX group and control group that the lowest value was in the control group. In CAD group, hs-CRP was positively correlated with NLR (r = 0.43, p < 0.001), and Gensini score (r = 0.54, p < 0.001). NLR was also linearly correlated with Gensini score (r = 0.49, p < 0.001). In ROC curve analysis, for the NLR of 2.26, NLR values attained 85.5% sensitivity and 43.9% specificity (p < 0.001). When cut-off value was taken as 3.05 mg/dL for CRP, CRP values attained 78.7% sensitivity and 43.6% specificity (p < 0.001). When cut-off value was taken as 9.5 (×109 /L) for white blood cell (WBC), WBC values attained 58.8% sensitivity and 34.3% specificity (p < 0.001). Conclusions: NLR seems to be usefull in prediction of obstructive CAD and can be implemented in planning for diagnostic procedures in patients with typical chest pain. Increased CRP, WBC and NLR may give insight about main pathology of CSX. Despite absence of obstructive narrowing in epicardial coronaries, it appears be salutary to treat CSX due to the similar underlying pathophysiology with obstructive CAD.